WAHYU WIDODO - admin, Keguru (Penerbit STKIP PGRI Bangkalan, 2019)
ABSTRACTThis paper describes the effect of CASE program to elementary student cognitive development. The study used a sequential explanatory design with the quantitative data collection in the first phase followed by collection of qualitative data in the second phase. Participants were 70 year 5 elementary school (ages 10-12) students. Quantitative data were collected by Scientific Reasoning Skill Tasks administered to all of participants both before and after intervention. Qualitative data included interviews with the five participants from CASE group and four participants from control group. Over 3 month period, students from the intervention group had higher mean gain (mean RGS = 4.4) compared with control group (mean RGS = 0.1). The qualitative data indicated CASE program were very effective because students motivation and regulation increased siginficantly after the intervention. Moreover, teacher developed more specific strategy to enhance students cognitive ability. To sum up, CASE program was a worthwhile intervention for Indonesian school especialy on elementary level students.